2020
DOI: 10.4271/2020-01-0788
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of the Combustion Process inside a Large-Bore Dual-Fuel Two-Stroke Marine Engine by Using Multiple High-Speed Cameras

Abstract: <div class="section abstract"><div class="htmlview paragraph">Dual-fuel engines for marine propulsion are gaining in importance due to operational and environmental benefits. Here the combustion in a dual-fuel marine engine operating on diesel and natural gas, is studied using a multiple high-speed camera arrangement. By recording the natural flame emission from three different directions the flame position inside the engine cylinder can be spatially mapped and tracked in time. Through space carvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, using two separated tables is not recommended when diesel fuel is injected into a premixed air-NG mixture. In a recent study, Hult et al [6] conducted an experimental study on the dual-fuel MAN 4T50ME-X test engine. They compared the flames of dual-fuel and a diesel engine and concluded that the flame length development is similar for two flames because the gas injection system was tuned to achieve a similar combustion rate as the diesel engine mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using two separated tables is not recommended when diesel fuel is injected into a premixed air-NG mixture. In a recent study, Hult et al [6] conducted an experimental study on the dual-fuel MAN 4T50ME-X test engine. They compared the flames of dual-fuel and a diesel engine and concluded that the flame length development is similar for two flames because the gas injection system was tuned to achieve a similar combustion rate as the diesel engine mode.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the flames of dual-fuel and a diesel engine and concluded that the flame length development is similar for two flames because the gas injection system was tuned to achieve a similar combustion rate as the diesel engine mode. However, the lift-off length (which is defined in [6] as the smallest distance from injector to where soot starts form) for the gas flame has a higher value than diesel.…”
Section: Introductionmentioning
confidence: 99%